Pengaruh Nilai Tukar Rupiah, IHSG, dan Yield Obligasi terhadap Indeks Harga Saham Energi dengan Harga Batubara Dunia sebagai Variabel Moderator - Nico Nico; Helma Malini; Mochammad Ridwan Ristyawan (Jurnal Ragam Pengabdian, 2026)
IDX Energy's movement on the Indonesian Stock Exchange is an important reflection of the health of the national energy industry amidst global market volatility. This research aims to analyze the influence of the Rupiah Exchange Rate, IHSG, and Bond Yield on IDX Energy, as well as testing the role of World Coal Prices as a moderating variable. The data used is monthly time series data throughout the 2021–2025 observation period with a total of 60 observations. The econometric analysis framework integrates ECM and MRA approaches that have passed the diagnostic test qualifications of classical assumptions and Engle-Granger cointegration. Short-term estimation results show that only IHSG has a positive and significant influence on energy sector stock returns, which confirms the enactment of mass market behavior. In contrast, the Rupiah Exchange Rate and Bond Yield did not show a significant influence, indicating the structural rigidity of issuers and strong market segmentation in Indonesia. Furthermore, World Coal Prices have proven to fail to act as a moderating variable in all baseline relationships due to the dampening effect of market mechanisms on the monthly horizon. This research recommends short-term investors to focus analysis on aggregate market movements (IHSG) and the issuer's internal performance.